2023
DOI: 10.1186/s12885-023-11670-z
|View full text |Cite
|
Sign up to set email alerts
|

Assessing health-related quality of life among cancer survivors during systemic and radiation therapy in Bangladesh: a cancer-specific exploration

Md. Shahjalal,
Marufa Sultana,
Jeff Gow
et al.

Abstract: Background Evaluating the effects of cancer diagnosis and treatment on a patient’s overall well-being is crucial and health-related quality of life (HRQoL) is a reliable metric for assessing this impact. Little is known about HRQoL among cancer survivors across various stages and treatments. The study examined individual and clinical factors influencing HRQoL among cancer survivors. Methods A cross-sectional study was conducted in two specialised c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…The odds of poor QoL among prostate cancer patients treated in public hospitals increased by 35% as compared to private institutions. This finding is supported by the previous literature [ 39 , 40 ]. This might be due to the fact that private institutions often had better resources and facilities and provided better access to patients compared to the public.…”
Section: Discussionsupporting
confidence: 93%
“…The odds of poor QoL among prostate cancer patients treated in public hospitals increased by 35% as compared to private institutions. This finding is supported by the previous literature [ 39 , 40 ]. This might be due to the fact that private institutions often had better resources and facilities and provided better access to patients compared to the public.…”
Section: Discussionsupporting
confidence: 93%
“…Studies either implicate cancer therapy, 20 or implicate cancer stage in affecting physical functioning domains. 21 However, other studies found no differences in overall QoL by cancer stage. 22 , 23 …”
Section: Introductionmentioning
confidence: 93%
“…41 It is important to point out that people with metastatic cancer have lower quality of life, which is linked to poorer treatment outcomes. 42 Therefore, the authors emphasise that causality must be established through further causal inferential studies.…”
Section: Bmj Public Healthmentioning
confidence: 99%